Analisa Kekerasan Baja Pegas Terhadap Pengaruh Pemanasan Nyala Api - Heri Wahyudi Kurniawan; Vita Ambarwatai; Meryanalinda Meryanalinda (JURAL RISET RUMPUN ILMU TEKNIK, 2024)
Spring steel is one type of material that is widely used in various engineering applications, such as vehicle suspension systems and equipment that require resistance to dynamic loads. Spring steel possesses various mechanical characteristics that are strongly influenced by the microstructure of the material. These characteristics remain consistently affected throughout the entire material. Heating that occurs due to exposure to flame can alter certain microstructural properties of spring steel and affect its performance. In this study, an analysis was carried out on all changes in the microstructure of spring steel caused by flame heating, as well as its effect on the hardness of the material. The results of the study showed that heating can indeed cause changes in the microstructural phase and a decrease in fatigue resistance of the spring steel.